The CEO's Influence on Corporate Foundation Giving - Werbel, James D. (Journal of business ethics, 2002)
Some scholars have argued that CEOs may have excessive influence on their foundation's trustees to give away a portion of company profits to charitable causes in order to gain access to elite circles or support the CEO's personal causes. This may result in charitable contributions that ultimately serve the personal interests of the CEOs without regard to corporate interests or social needs. We examine the extent that CEOs appear to direct charitable giving to be compatible with their own personal interests, and if CEO participation on the foundation board affects the relationship between CEO personal interests and charitable giving. Using a sample of 160 corporate foundations, our results showed that CEOs' interests, as measured by membership in different non-profit organizations, was associated with foundation charitable giving. This association decreased, but was not eliminated, when CEOs were absent from the foundation board. Implications of these findings for researchers and managers are discussed in regards to both agency theory and stewardship theory.